1996
DOI: 10.1021/cm960168c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Tunable Electronic/Optical Properties of II−VI Semiconductor Species Included in the Sodalite Structure

Abstract: The composition-dependent optical and electronic tunability of the sodalite analogues with stoichiometries Zn8X2[BO2]12 (X = O, S, Se) and [Cd y Zn(1-y)]8X2[BeSi x Ge(1-x)O4]6 (X = S, Se and Te) have been demonstrated. The materials strongly photoluminesce, and a comparison of the photoluminescence behavior of the single crystals with the as-synthesized powder analogues shows that the visible emission is intrinsic to the sodalite analogue and not due to impurities such as bulk semiconductor. The emission maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…On the 3-fold axes of each large cavity, 3.0 In + ions at In(1) and 0.5 In 3+ ions at In(8) lie opposite six-rings within the primary coordination spheres of framework oxygens, whereas 0.5 In + ions at In(10) are located deep in large cavity, probably as InSH molecules stabilized by sorbed H 2 S molecules and In + ions (see sections 4.3 and 4.4). On the 3-fold axes of each sodalite unit, 2.0 In 1.75+ ions at In (2) and 0.5 In + ions at In(3) are found opposite six-rings, as seen in previously reported crystal structures of In 11 -A and In 8.75 -A(S 2 ). 11,15 Near the eight-rings of each unit cell, a total of 2.5 more In + ions are found at three different Wyckoff positions (1.0, 0.5, and 1.0 at In(4), In (5), and In(9), respectively), where they are extensively involved in the stabilization of newly formed and sorbed molecules deep in large cavity (see sections 4.3 and 4.4).…”
Section: 3) a Stereoview Of The Large Cavity Of Unit Cell 2 Is Shosupporting
confidence: 79%
See 3 more Smart Citations
“…On the 3-fold axes of each large cavity, 3.0 In + ions at In(1) and 0.5 In 3+ ions at In(8) lie opposite six-rings within the primary coordination spheres of framework oxygens, whereas 0.5 In + ions at In(10) are located deep in large cavity, probably as InSH molecules stabilized by sorbed H 2 S molecules and In + ions (see sections 4.3 and 4.4). On the 3-fold axes of each sodalite unit, 2.0 In 1.75+ ions at In (2) and 0.5 In + ions at In(3) are found opposite six-rings, as seen in previously reported crystal structures of In 11 -A and In 8.75 -A(S 2 ). 11,15 Near the eight-rings of each unit cell, a total of 2.5 more In + ions are found at three different Wyckoff positions (1.0, 0.5, and 1.0 at In(4), In (5), and In(9), respectively), where they are extensively involved in the stabilization of newly formed and sorbed molecules deep in large cavity (see sections 4.3 and 4.4).…”
Section: 3) a Stereoview Of The Large Cavity Of Unit Cell 2 Is Shosupporting
confidence: 79%
“…As atoms, they may preferentially approach cations, to which they could delocalize electron density, rather than framework oxygens. Indeed, they are reasonably close to the indium cations at In (2) and In(3) in the sodalite units. These In 0 atoms at In(6) might have been retained during the reaction between In 0 and Tl-A, or might have been produced by disproportionation during later exposure to the atmosphere or to hydrogen sulfide, or both.…”
Section: Indium Atoms and Clustersmentioning
confidence: 55%
See 2 more Smart Citations
“…The synthesis conditions and reagents can be used to control the sizes and morphologies of nanoparticles. As a result, syntheses of monodispersed II-VI semiconductor nanoparticles have attracted a great deal of interest due to the potential applications of these nanoparticles as non-linear optical materials, [1] in devices, for biomedical imaging [2] and as photovoltaics. [3] There are many studies which have reported wet chemical syntheses of CdSe.…”
Section: Introductionmentioning
confidence: 99%